Behaviour of a speargun with a novel muzzle - V. Nigrelli; M. Mucera; T. Ingrassia (Fracture and Structural Integrity)
The paper presents the results of a numerical and experimental investigation performed on a barrel of a speargun equipped with two kinds of muzzle. In particular, a standard muzzle for speargun (having an elastic propulsion) has been compared with an innovative one called ‘roller’. This new muzzle is equipped with two rollers and special bands. The rubber bands, fixed at the lower side of the barrel, run through the rollers and are engaged in suitable seats of the shaft. These bands are, therefore, longer than the traditional ones and, consequently, with equal force applied by the diver, the roller speargun has a longer range. Thanks to the particular geometry of the new muzzle, one of the front constraints of the elastic bands is moved to the lower part of the barrel or the handle.As a consequence, the scheme of the loads applied on the speargun remarkably changes passing from a standard muzzle to a roller one. All that has a great influence on the level of deformation of the barrel and, consequently, on the accuracy of the shot. Because of the low velocity of the spear (if compared with the firearms), in fact, the accuracy of the shoot if strongly influenced by the barrel bending due to the forces applied by means of the elastic bands. In this paper it is experimentally evaluated the bending of the barrel equipped both with the innovative muzzle and with the traditional one in order to compare their performances. The experimental analysis of the barrel was performed by electrical strain gauges suitably located at the section with the highest values of the strains. In order to find the barrel section with the highest strain values where to locate the strain gauges, a preliminary numerical FEM analysis has been performed. The loads and constraints scheme has been evaluated both for the standard and the new muzzle. In particular, the forces due to the elastic bands, their application points and directions have been experimentally obtained. To speed up the process of numerical simulation, without invalidating the results reliability, simplified FEM models have been used. In particular, a very accurate model of the barrel has been shaped, whereas the models of the muzzles and the handle have been simplified. The forces due to the elastic bands, experimentally obtained, have been applied on the FEM models. The maps of the maximum and minimum principal strains have allowed to find the area with the highest strain values, placed in rear part of the barrel (near the handle). The strain values experimentally measured on the speargun have been very similar to the ones calculated by means of the numerical simulations. That demonstrates the developed FEM models are very reliable and can ben used to predict the performances of the speragun under different loads conditions. The speargun with the new roller muzzle shows very lower strain values if compared with the ones measured in the standard one. Nevertheless, considering the two spearguns have different elastic bands setup, it has been thought the comparison of their performances should be made hypothesizing the same maximum force applied during the speargun charge. This condition, moreover, could be really obtained by changing the kind of the elastic bands in the speargun with the roller muzzle. For this reason, during the results analysis phase, the strain values measured on the roller speargun have been ‘normalized’ by increasing them of a value equal to the ratio of the maximum forces due to the rubber bands. The data post processing has allowed to evaluate the forces and the bending moments on the barrels with the standard muzzle and the roller one. Results show the barrel with the innovative muzzle has, also considering equal forces applied by the diver, a lower bending than the barrel with a traditional muzzle. To evaluate the maximum deflection of both the spearguns, a new numerical simulation has been set up. In particular, in this FEM analysis, the roller speargung has been loaded with a maximum force comparable with the standard one. The obtained results show that the standard speargun has a higher value of the maximum deflection respect to the roller one. Since higher deflection values of the barrel make worse the accuracy of the shot, these results demonstrate the novel speargun can be more precise than the traditional one.